Endowment Effect and Reservation Wage: A behavioural evaluation of the impact of 2010 Jobseekers Allowance rate changes on labour market outcomes for young unemployed - Doyle, Eric (Journal of the Statistical and Social Inquiry Society of Ireland, 2018)
This paper evaluates the impact of the 2010 jobseekers allowance rate changes on the labour market decisions of new jobseekers to investigate the predictive power of orthodox versus behavioural economic theories. The paper tests the degree to which the endowment effect and loss aversion acts to subvert optimising behaviour as specified by the orthodox economic job-search model. The study found that jobseekers demonstrated optimising behaviour when faced with a reduction in their welfare support through increased employment exits. The results provide ambiguous evidence to support the predictions concerning previous earnings and endowment effect or loss aversion. The results provide no evidence for the policy rationale regarding incentivising greater take up of activation or education amongst young jobseekers.
read before the Society, 31 May 2018
Keywords: youth unemployment; labour markets; welfare; 314.15